2010
DOI: 10.3371/csrp.4.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Stigma, Self-Esteem, and Symptoms with Concurrent and Prospective Assessment of Social Anxiety in Schizophrenia

Abstract: Rationale Often overlooked clinically, social anxiety is common in schizophrenia and may represent a barrier to quality of life and social function. Little is known, however, about the possible roots of social anxiety in schizophrenia or their relationship to social anxiety over time. Methods To explore this issue, we examined the relationship between self-esteem, self-stigma, positive and negative symptoms, emotional discomfort and affect recognition with concurrent and prospective assessments of social anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 49 publications
5
47
1
1
Order By: Relevance
“…On the other hand, positive symptoms, depression and general psychopathology were mostly found to correlate significantly with personal stigma. However, no illness‐related variable was unequivocally correlated with personal stigma, except for social anxiety, which was only assessed in two studies, one on perceived stigma and one on self‐stigma . These results are in line with another study that was excluded from our review due to the heterogeneity of its sample .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, positive symptoms, depression and general psychopathology were mostly found to correlate significantly with personal stigma. However, no illness‐related variable was unequivocally correlated with personal stigma, except for social anxiety, which was only assessed in two studies, one on perceived stigma and one on self‐stigma . These results are in line with another study that was excluded from our review due to the heterogeneity of its sample .…”
Section: Discussionsupporting
confidence: 79%
“…As in chronic samples, patients in the first episode showed increased perceived stigma when they had social anxiety . This does not differ from the results concerning the relationship of self‐stigma and social anxiety in a sample of elderly patients with multiple illness episodes (mean age=64.7, SD=8.7) . Likewise, the results of the second sample of patients with first‐episode psychosis concerned prevalence rates and the relationship between positive symptoms and perceived stigma , and they did not differ from results regarding patients in later disease stages .…”
Section: Resultscontrasting
confidence: 48%
“…Social withdrawal, which is a prominent aspect of the motivation component of negative symptoms, may partially reflect anxiety (Birchwood, 2003;Chudleigh et al, 2011;Lysaker et al, 2010;Penn et al, 1994), whereas diminished expressiveness appears unrelated to anxiety (Cohen et al, 2012;Huppert and Smith, 2001;Kelley et al, 1999). There is also evidence that the motivational component has more implications for everyday functioning than diminished expression Green et al, 2012;Rocca et al, 2014;Sayers et al, 1996;Strauss et al, 2013), although these findings may be confounded by the prominence of observed functioning in the assessment of negative symptoms related to motivation (Leifker et al, 2009;Ventura et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…В груп-пе больных шизофренией социальная тревожность связана преимуществен-но с реакциями избегания при чувстве стыда . По данным зарубежных исследо-ваний именно чувство стыда, возникаю-щее в связи со стигматизацией при за-болевании, является определяющим для социальной тревожности у больных ши-зофренией, в отличие от социальной тревожности у здоровых людей (Lysaker, 2010;Birchwood, 2006) .…”
Section: обсуждение результатовunclassified